2013
DOI: 10.1055/s-0033-1348893
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Contraceptive Access and Provision

Abstract: Even though contraceptive coverage expands under the Patient Protection and Affordable Care Act, reducing disparities in contraceptive access and provision requires that all providers assess their patient's reproductive life plans and that health systems work to minimize institutional and socioeconomic barriers. In this article, the challenges of providing equal access to contraceptive care, as well as recommendations for encouraging the use of effective contraception among all reproductive age women are revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 213 publications
(236 reference statements)
0
11
0
Order By: Relevance
“…The CHOICE study clearly demonstrated that unintended pregnancy rates can be dramatically reduced by eliminating financial barriers. When cost is not a factor this study found that 75 % of eligible women chose a LARC method [ 53 ]. Although multiple studies have shown that investment in contraception leads to significant cost-savings, access to LARC methods by poor women remains challenging.…”
Section: Worldwide Usementioning
confidence: 99%
“…The CHOICE study clearly demonstrated that unintended pregnancy rates can be dramatically reduced by eliminating financial barriers. When cost is not a factor this study found that 75 % of eligible women chose a LARC method [ 53 ]. Although multiple studies have shown that investment in contraception leads to significant cost-savings, access to LARC methods by poor women remains challenging.…”
Section: Worldwide Usementioning
confidence: 99%
“…Historically, the United States has had a shameful history regarding forced sterilizations and reproductive injustices which may lead minority women to be distrustful of contraception [14,15]. There are also racial differences in contraceptive preferences.…”
Section: Disparities In Unintended Pregnancy and Access To Carementioning
confidence: 99%
“…African-American and Latina women suffer from misconceptions surrounding contraception, its use and efficacy [14]. The CHOICE project serves an example of using patient education to effectively overcome cultural beliefs that pose a barrier to the use of highly efficacious contraception.…”
Section: Culturally Sensitive Approachmentioning
confidence: 99%
See 2 more Smart Citations